Insights into lipid metabolism and immune-inflammatory responses in the pathogenesis of coronary artery ectasia - Jiang, Li; Wei, Wei; Kang, Sheng; Li, Xiao-Lin; Luo, Yu (Frontiers in Physiology, 2023)
Coronary artery ectasia (CAE) is a rare finding that is associated with poor clinical outcomes (Kawsara, Nunez Gil et al. 2018), and disorders in lipid metabolism have been reported in CAE. Lipids constitute one of the three metabolite types that regulate bodily functions and are also powerful signaling molecules (Han 2016, Zhu, Zhou et al. 2021) that affect immunoregulation and inflammatory responses via a series of transcription factors and signaling pathways (Barrera, Zhou et al. 2013). Although abnormal lipid metabolism and immunoinflammatory responses have been reported in CAE, their roles in the pathogenic mechanisms underlying CAE are currently unclear.